Micro downtimes management in the Lean perspective: An empirical research in a production bottleneck - Lacerda, Pedro; Guedes Ramos, Maria Clara; Odebrecht de Souza, Raphael; Bonamigo, Andrei; Forcellini, Fernando Antônio (International Journal of Industrial Engineering and Management, 2025)
Nowadays, in the present dynamic industrial scenario characterized by shorter product lifecycles, customization, and uncertain demand, corporations should enhance their efficiency by reducing waste to remain competitive. This research addresses machine micro downtimes, which embrace a significant waste source that negatively affects Overall Equipment Effectiveness (OEE). Although the literature presents some studies suggesting methods to mitigate micro downtimes, contemporary approaches focus on isolated strategies, lacking an integrated methodology. Accordingly, a research gap remains in developing a comprehensive framework that holistically improves OEE and systematically decreases micro downtimes within processes with bottlenecks. In this context, the objective of this study is twofold. First, we aim to introduce a Lean-based framework to reduce micro downtimes in manufacturing processes. Second, we present the results of applying this framework in a Brazilian tire company through a practical research approach. The results demonstrate a 1.6% reduction in machine micro downtimes, amounting to potential savings of USD 750,000 annually. Additionally, the implementation led to the improvement project's completion three weeks ahead of schedule, showcasing the framework's effectiveness. Article history: Received (June 13, 2024); Revised (December 24, 2024); Accepted (March 4, 2025); Published online (April 10, 2025)